Analysis of p2p communication over various mobile platforms - Abd Rahman, Akmal Nurhananie; Habaebi, Mohamed Hadi; Jarot, Sigit Puspito Wigati; Chebil, Jalel; Ismail, Mahamod (INSI Publications, 2013)
The peer-to-peer (P2P) file sharing protocol has evolved from depending on Internet connection provided by the cellular network, to free Internet connectivity through Wi-Fi technology. Yet it incurs other problems, especially with regards to its energy-efficiency. This paper analyses the current P2P protocols that have been adopted on different mobile platforms, including Android, Symbian, iOS, Blackberry, and Windows Mobile OS, as well as tablets with different operating systems (OS), based on their reliability, delay-guarantee, rate-efficiency and energyefficiency. The analysis involves P2P protocols through various communication interfaces, which require Internet connectivity (i.e., WiFI) the ones that avoid Internet connection altogether, (i.e., P2P protocols over the IEEE 802.15 PAN standards Bluetooth, UWB, RFID, and ZigBee).